Dissolved 222rn and 226ra in groundwaters of guarani aquifer system and serra geral aquifer at Ribeirão Preto City, São Paulo State, Brazil - Lara, Felipe Mangili [UNESP]; Galhardi, Juliana Aparecida [UNESP]; Bonotto, Daniel Marcos [UNESP] (My University, 2015)
Radon (222Rn, half-life 3.8 days) is a naturally occurring volatile noble gas formed from the normal radioactive decay series of 238U, according to the following decay sequence: 238U (4.49 Ga, α) → 234Th (24.1 d, β-) → 234Pa (1.18 min, β- ) → 234U (0.248 Ma, α) → 230Th (75.2 ka, α) → 226Ra (1622 a, α) → 222Rn (3.83 d, α) → ... Radon is colorless, odorless, tasteless, chemically inert and radioactive gas produced continuously in rocks and soils through α-decay of 226Ra, with some atoms escaping to the surrounding fluid phase, such as groundwater and air. It is subjected to recoil at birth, with the emanated fraction relatively to that produced in the solid phase being dependent on factors such as total surface area of solids and concentration/distribution of 238U (226Ra) in the minerals. 222Rn decays to stable lead according to the sequence: 222Rn (3.83 d, α) → 218Po (3.05 min, α) → 214Pb (26.8 min, β-) → 214Bi (19.7 min, β-) → 214Po (0.16 ms, α) → 210Pb (22.3 a β-) → 210Bi (5 d, β-) → 210Po (138.4 d, α) → 206Pb. This chapter reports the 222Rn and 226Ra activity concentration in groundwater samples of Guarani and Serra Geral aquifers in the city of Ribeirao Preto, state of São Paulo, Brazil. The 222Rn average activity concentration for the Guarani aquifer was 0.79 BqL-1, whereas the 226Ra average activity concentration was 0.10 BqL-1. For the Serra Geral aquifer, these values were 1.00 BqL-1 and 0.22 BqL-1, respectively. The results indicate differences in the chemical and radiological aspects between the two aquifers, due to its different geological conditions. Possible mixture of waters was verified in the region as the radon and radium activity concentration were more pronounced at the fractured than in the sedimentary aquifer. No sample exhibited higher radon and radium activity concentration than the guideline values established by the health agencies.